Annexin a1 mimetic peptide and piperlongumine: Anti-inflammatory profiles in endotoxin-induced uveitis - Girol, Ana Paula [UNESP] (2021)
Uveitis is one of the main causes of blindness worldwide, and therapeutic alternatives are worthy of study. We investigated the effects of piperlongumine (PL) and/or annexin A1 (AnxA1) mimetic peptide Ac2-26 on endotoxin-induced uveitis (EIU). Rats were inoculated with lipopolysac-charide (LPS) and intraperitoneally treated with Ac2-26 (200 µg), PL (200 and 400 µg), or Ac2-26 + PL after 15 min. Then, 24 h after LPS inoculation, leukocytes in aqueous humor, mononuclear cells, AnxA1, formyl peptide receptor (fpr)1, fpr2, and cyclooxygenase (COX)-2 were evaluated in the ocular tissues, along with inflammatory mediators in the blood and macerated supernatant. Decreased leukocyte influx, levels of inflammatory mediators, and COX-2 expression confirmed the anti-inflammatory actions of the peptide and pointed to the protective effects of PL at higher dosage. However, when PL and Ac2-26 were administered in combination, the inflammatory potential was lost. AnxA1 expression was elevated among groups treated with PL or Ac2-26 + PL but reduced after treatment with Ac2-26. Fpr2 expression was increased only in untreated EIU and Ac2-26 groups. The interaction between Ac2-26 and PL negatively affected the anti-inflammatory action of Ac2-26 or PL. We emphasize that the anti-inflammatory effects of PL can be used as a therapeutic strategy to protect against uveitis.